Pengaruh Live Streaming, Countdown, dan Influencer Terhadap Impulsive Buying pada Pengguna TikTok Shop dengan Emotional Arousal sebagai Variabel Mediasi - Ferdila Ayu Wandansari; Andi Muhammad Sadat; Rizka Zakiah (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of live streaming, countdown timers, and influencers on impulsive buying among TikTok Shop users, with emotional arousal serving as a mediating variable. The research employed a quantitative approach using a survey method. The population consisted of TikTok Shop users in Indonesia aged 17 years and above who had purchased products through the live streaming feature at least twice within the last three months and resided in the Greater Jakarta area (Jabodetabek). A non-probability sampling technique with a purposive sampling method was used, resulting in a sample of 290 respondents. Data were collected through a questionnaire using a Likert scale. This study was based on the Stimulus–Organism–Response (S-O-R) theory, which explains the relationship between external stimuli, individuals’ internal psychological states, and their behavioral responses. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach and processed using SmartPLS version 4. The results indicate that Live Streaming (LS), Countdown Timers (C), Influencers (IF), and Emotional Arousal (EA) have positive and significant effects on Impulsive Buying (IB). Furthermore, Live Streaming (LS), Countdown Timers (C), and Influencers (IF) have positive and significant effects on Emotional Arousal (EA). The findings also reveal that Emotional Arousal (EA) significantly mediates the effects of Live Streaming (LS), Countdown Timers (C), and Influencers (IF) on Impulsive Buying (IB).